Lower Insulinic Resistance on High Altitude Obese Inhabitants - Jo, Nancy (1997)
It has been demonstrated that obesity produces insulin resistance, dislipidemia, high blood pressure and other metabolic alterations which are risk factors to develop atherosclerosis and cardiovascular events. On the other land, chronic expossure to high altitude increases the insulin sensibility; the blood glucose concentration, total and LDL cholesterol are lower in high altitude dwellers than in sea level inhabitants, and HDL cholesterol is higher. Therefore, it seemed interesting to study the metabolic events in the obese people living at high altitude. A total of 41 male obese, aged 20 to 60 years, were studied; 11 living at sea level (Lima, 150 m above sea level) and 30 living at high altitude (Huancayo 3200 m above sea level). Oral glucose tolerance tests consisting in 75 g were conducted in these subjects. Anthropometric measures (height, weight, body mass index, abdominal ship index) as well as blood glucose, total and HDL cholesterol, triglycerldes and insulin were measured. LDL and VLDL were calculated following the Friedewald's formula. Blood glucose, and insulin were significantly lower 2 hours after the glucose administration in the high altitude obese subjects demonstrating that obese subjects at high altitude have a lower insulin resistance, which is also supported by the higher HDL2 concentration, lower blood pressure and no hypertensive subjects. These results demonstrate that exposition to high altitude lowers the insulin resistance and the accompaning metabolic and clinical events even in obese subjects.